Structural damage characteristics and mechanism of granite residual soil - Lu Yiwei; Shi Yujie; Chen Bin; Feng Zihao; Hu Jieming (Applied Rheology, 2024)
Deep and thick weathered granite crusts widely distributed in Xiangdong area, Hunan Province, due to their special structure, often induce geological disasters such as landslides under the conditions of excavation or atmospheric precipitation. In this article, using the direct shear test, X-ray diffraction test and scanning electron microscope test, the mechanical properties and the response mechanism of the microstructure of the granite residual soil in eastern Hunan area under different states were studied, and the structural damage mechanism of the granite residual soil was analysed. Based on the comprehensive structural potential, the theory characterizes its structure. The results show that the granite residual soil is mainly composed of minerals such as quartz, mica, kaolinite and feldspar, and it also contains a small amount of chlorite and calcite. The damage is mainly reflected in the attenuation of cohesion, while the change of the internal friction angle is small. The microscopic manifestation is the failure of the bridging structure between the aggregates, and the inter-granular pores are interconnected. The difference and shear strength response reflect the susceptibility to disturbance of granite residual soil and reflect that the structural strength has been damaged under the disturbance of human factors.